2002
DOI: 10.1080/00039420215637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Carnitine Supplementation on Utilisation of Energy and Protein in Broiler Chicken Fed Different Dietary Fat Levels

Abstract: Effects of a supplementation of 80 mg L-carnitine per kg diet were studied in broiler chicken at two dietary levels of fat (4 and 8%) and different feeding levels (ad libitum in a growth trial, 95 and 85% of ad libitum in a balance trial). A low-carnitine basal diet adequate in amino acid concentration was used. In the growth trial, each diet was fed to 9 groups of 10 birds each for 16 days from day 5 of live onwards. Growth and feed intake were determined. At the end of the trial, birds were killed and homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
4
16
0
1
Order By: Relevance
“…This level significantly improved the FCR and is similar to reports by (Rabie et al, 1997) and (Rodehutscord et al, 2002). Other studies reported finding no effect of L-carnitine on FCR (Barker and Sell, 1994;Buyse et al, 2001;Lien and Horng, 2001).…”
Section: Effects Of L-carnitine and Gemfibrozil On Broiler Performancesupporting
confidence: 90%
“…This level significantly improved the FCR and is similar to reports by (Rabie et al, 1997) and (Rodehutscord et al, 2002). Other studies reported finding no effect of L-carnitine on FCR (Barker and Sell, 1994;Buyse et al, 2001;Lien and Horng, 2001).…”
Section: Effects Of L-carnitine and Gemfibrozil On Broiler Performancesupporting
confidence: 90%
“…Some reports showed that L-carnitine supplementation improved BWG (Rabie et al 1997;Rabie & Szilagyi 1998), but some others showed that there were no positive effects of L-carnitine supplementation on broiler's growth performance (Buyse et al 2001;Rodehutscord et al 2002). Ç elik and Ö ztü rkcan (2003) even indicated that L-carnitine or L-carnitine þ ascorbic acid supplementation reduced BWG of broiler chicks under thermoneutral condition.…”
Section: Discussionmentioning
confidence: 93%
“…The role of L‐carnitine dietary supplementation on growth promotion has been verified in different species such as broilers (Rodehutscord et al . ; Zhan et al . ; Khadem et al .…”
Section: The Physicochemical Properties Of L‐carnitine and Its Generamentioning
confidence: 99%